NATURE INSPIRED SYNTHESIS, PHYSICO-CHEMICAL CHARACTERIZATION OF Zn DOPED Fe3O4 NANOPARTICLES USING ANDROGRAPHIS PANICULATA (BURM. F.) NEES LEAF EXTRACT AND ASSESSMENT OF IN VITRO PANCREATIC ALPHA AMYLASE INHIBITORY ACTIVITY - ATHITHAN, A. S. SAKTHI; JEYASUNDARI, J.; RENUGA, D.; NAVEENA, A. (International Journal of Applied Pharmaceutics, 2020)
Objective: Magnetite (Fe3O4) nanoparticles (NPs) have gained considerable attention in the Biomedical filed. Evolution of new magnetic material based on the transition metal-doped magnetite has become the subject of increasing research interest. The main aim of the current investigation was to improve the diabetic potential, optical, magnetic, structural properties of magnetite nanoparticles and hence Fe3O4 NPs were doped with a divalent transition element such as Zinc. Methods: Zinc doped magnetite nanoparticles (Zn-Fe3O4 NPs) were obtained through Co-precipitation methods using aqueous plant extract of Andrographis paniculata acted as an efficient stabilizer and a reducing agent. The structure, morphology, crystalline, optical and magnetic property of synthesized Zn-Fe3O4 NPs were evaluated by X-ray diffraction (XRD), Scanning electron microscopy with Energy dispersive x-ray spectroscopy(SEM-EDX), Fourier transform infrared spectroscopy (FTIR), Ultraviolet-Visible (UV-Vis) Spectrophotometer and Vibrating scanning magnetometer (VSM). Results: In XRD analysis, the average crystallite size of the synthesized Zn-Fe3O4 NPs was found to be 5 nm exhibiting super paramagnetic behavior, which composes it an appealing possibility for biomedicines. The Zn-Fe3O4 NPs had strongly inhibited the alpha (α)-amylase enzyme and had proved their therapeutic role. Conclusion: In conclusion, Zn-Fe3O4 NPs is an excellent anti-diabetic agent to control type 2 diabetes mellitus.